2008
DOI: 10.1002/ejoc.200800203
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Cystothiazole A by Microwave‐Assisted Olefin Cross‐Metathesis

Abstract: A short and convergent synthesis of the myxobacterial antibiotic cystothiazole A by a microwave-assisted olefin crossmetathesis reaction and a sequential microwave-assisted cross-metathesis/Stille coupling is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…378 Through a microwaveassisted olefin cross-metathesis reaction, an alternative total synthesis of cystothiazole A 431 was achieved. 379 Melithiazole C 438, a special member of the melithiazols containing only a single thiazole ring, has also been highly efficiently synthesized based on a ring closure metathesis (RCM) strategy catalyzed by the 2nd Grubbs catalyst or the Hoveyda-Grubbs catalyst. 380 Since its recent isolation from a cyanobacterium of the genus Symploca sp., a scarcely investigated species, largazole 439 has received extensive interest from synthetic chemists due to its significant selective antitumor activity combined with unique structural characteristics, including a substituted 4-methylthiazoline linearly fused to a thiazole ring and a thioester moiety.…”
Section: Phytoalexinsmentioning
confidence: 99%
“…378 Through a microwaveassisted olefin cross-metathesis reaction, an alternative total synthesis of cystothiazole A 431 was achieved. 379 Melithiazole C 438, a special member of the melithiazols containing only a single thiazole ring, has also been highly efficiently synthesized based on a ring closure metathesis (RCM) strategy catalyzed by the 2nd Grubbs catalyst or the Hoveyda-Grubbs catalyst. 380 Since its recent isolation from a cyanobacterium of the genus Symploca sp., a scarcely investigated species, largazole 439 has received extensive interest from synthetic chemists due to its significant selective antitumor activity combined with unique structural characteristics, including a substituted 4-methylthiazoline linearly fused to a thiazole ring and a thioester moiety.…”
Section: Phytoalexinsmentioning
confidence: 99%
“…Cystothiazole A, one of the most important members of bb-MOAs, was isolated from the myxobacterium Cystobacter fuscus and showed excellent antifungal activities against a broad range of fungi including the phytopathogenic fungus Phytophthora capsici and Candida albicans, and has thus become an attractive target for the development of new agrochemicals. Several stereoselective synthetic routes to cystothiazole A and related natural bb-MOAs have been reported [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Asymmetric Evans Aldol-based synthetic strategy with chiral oxazolidinone as auxiliary was applied by several groups [19][20][21][22]31,35] .…”
Section: Introductionmentioning
confidence: 99%
“…However, chemists' efforts to circumvent this problem have shown in recent literatures. For example, shorter reaction time and better yields were achieved by applying microwave irradiation [6,7,8]. One interesting approach was reported by Lipshutz's group: they found that copper (I) iodide is an effective additive for olefin cross-metathesis reactions [9].…”
Section: Introductionmentioning
confidence: 99%